2014
DOI: 10.1007/s00247-014-3181-z
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of expanded polytetrafluoroethylene-covered transjugular intrahepatic portosystemic shunts in children with acute or recurring upper gastrointestinal bleeding

Abstract: The safety profile and efficacy of expanded polytetrafluoroethylene (ePTFE)-covered TIPS were satisfactory in this small series of children with acute or recurrent gastrointestinal bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 20 publications
4
27
3
Order By: Relevance
“…[3][4][5][6][7][8][9] For studies without a preponderance of patients with EHPVO, improved technical success rates are noted, ranging from 78 to 100%. [3][4][5][6][7][8] Type and frequency of complications similarly parallel the adult TIPS data, albeit with a greater need for reintervention in some series. 3,5 Reported complications include intra-and post-procedural bleeding, TIPS thrombosis and stenosis, hepatic encephalopathy, IVC thrombosis, pulmonary edema, perforated roux-en-Y portoenterostomy, and death.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[3][4][5][6][7][8][9] For studies without a preponderance of patients with EHPVO, improved technical success rates are noted, ranging from 78 to 100%. [3][4][5][6][7][8] Type and frequency of complications similarly parallel the adult TIPS data, albeit with a greater need for reintervention in some series. 3,5 Reported complications include intra-and post-procedural bleeding, TIPS thrombosis and stenosis, hepatic encephalopathy, IVC thrombosis, pulmonary edema, perforated roux-en-Y portoenterostomy, and death.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 Reported complications include intra-and post-procedural bleeding, TIPS thrombosis and stenosis, hepatic encephalopathy, IVC thrombosis, pulmonary edema, perforated roux-en-Y portoenterostomy, and death. [3][4][5][6][7][8][9]33 Following the advent and widespread adoption of partially covered stent-grafts, which now represent the prevailing conduit in pediatric and adult TIPS alike, two studies have demonstrated excellent results. Vo et al reported 100% technical success rate and 100% primary patency rate in 12 patients, with a limited mean follow-up of 40 months (range 4 days to 32 months).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 There is a gap in consensus in the role of TIPS in pediatric patients with portal hypertension, 2,5,7 The scope of training for interventional radiologists may lead to relative inexperience in either TIPS or pediatric interventional radiology. 8 While existing results support the use of TIPS in pediatric patients with portal hypertension, 7,[9][10][11][12][13][14][15][16] the currently available case series are small and retrospective, ranging from 1 to 40 patients. 9,[17][18][19][20][21] Recently, Johansen et al published the largest single-center experience in 40 children and adolescents from Birmingham, UK, 21 and again demonstrated safety and effectiveness.…”
Section: Introductionmentioning
confidence: 99%